2021
DOI: 10.1177/14705958211004655
|View full text |Cite
|
Sign up to set email alerts
|

Thriving and retention of expatriates: Cultural intelligence and organizational embeddedness inputs

Abstract: Drawing on Conservation of Resources theory and the socially embedded model of thriving, we examine the resource antecedents and retention outcome of expatriate thriving. Using two-wave panel data from 103 international teachers in the United States, we found that the personal resource of cultural intelligence directly influenced thriving, and thriving led to expatriate actual retention. In addition, the contextual resource of organizational embeddedness served as a boundary condition that augmented cultural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
(125 reference statements)
0
3
1
Order By: Relevance
“…From the findings presented in Figure 2, it is evident that CI does not have a statistically significant influence on thriving at work. This finding contradicts the findings of Ren et al (2021), who found that CI, as a personal resource, had a direct influence on thriving at work. However, their sample consisted of expatriate teachers in the United States.…”
Section: Discussion and Practical Implicationscontrasting
confidence: 99%
“…From the findings presented in Figure 2, it is evident that CI does not have a statistically significant influence on thriving at work. This finding contradicts the findings of Ren et al (2021), who found that CI, as a personal resource, had a direct influence on thriving at work. However, their sample consisted of expatriate teachers in the United States.…”
Section: Discussion and Practical Implicationscontrasting
confidence: 99%
“…This tripartite conceptualization of adjustment has been validated in numerous studies (e.g. Ren et al, 2021). Abugre et al (2020) emphasized the importance of learning orientation during crosscultural adjustment of international expatriates.…”
Section: Learning Orientation and Expatriate Adjustmentmentioning
confidence: 89%
“…We tested for common method bias by employing the confirmatory factor analysis marker technique (Williams et al, 2010). As a marker variable, that is, a method factor that is theoretically unrelated to the substantive variables (Chadwick and Raver, 2020; Ren et al, 2021) and simultaneously likely to tap into at least one of the potential biases outlined by Podsakoff et al (2003), we used a three-item social desirability scale (Crowne and Marlowe, 1960; Cronbach’s alpha = 0.77). An example item for this scale is ‘I am sometimes irritated by people who ask favours of me’ (with responses ranging from 1 = strongly disagree to 7 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%